PENGARUH PENAMBAHAN NaOH TERHADAP UJI KUALITAS SABUN MANDI PADA EKSTRAK BUAH CIPLUKAN (PHYSALIS ANGULATA L) - Reny Evy; Nuril Wardatul Amaliyah; Qurrata A yun (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2022)
Ciplukan is a plant that has round fruit and is yellow-orange in color and has thin skin resembling petals, and usually grows in rice fields or river banks. The content of Flavonoids and vitamin C in ciplukan fruit is one of the natural antioxidant compounds that can be used as natural active substances in the manufacture of solid bath soap. One of the most important ingredients in the manufacture of solid body soap is NaOH, the volume of NaOH added to the formulation of solid body soap can affect the quality of the soap, namely pH, free alkali and water content. This study aims to determine the optimum volume of NaOH in the manufacture of solid soap. ciplukan fruit extract according to SNI. The research method that was carried out included several stages, namely sample preparation, making solid bath soap formulations with varying volumes of 10% NaOH (3 mL, 6 mL, 9 mL, 12 mL, 15 mL), and testing the quality of soap (testing water content, PH and foam stability). Based on the results of the soap quality test, a solid bath soap formulation of ciplukan fruit extract with a volume of 10% NaOH of 9 mL was obtained in accordance with SNI (water content 2.4%, pH 10, and foam stability 64.4%)